- 41

- 0

## Main Question or Discussion Point

Reference: www.mathpages.com/home367.htm[/URL]

On page 2 of reference the formula is given

(x+y)^p - x^p - y^p = pxy(x=y)Q(x,y) where Q(x,y) is a homogenous integer function of degree p-3.

If we insert a number of different value of p into the equation, it appears that

Q(x,y) = (x^2 = xy + y^2)^((p-3)/2)

Is there an easy way to prove this without getting lost in infinite series calculations, or is there a proof already in print?

On page 2 of reference the formula is given

(x+y)^p - x^p - y^p = pxy(x=y)Q(x,y) where Q(x,y) is a homogenous integer function of degree p-3.

If we insert a number of different value of p into the equation, it appears that

Q(x,y) = (x^2 = xy + y^2)^((p-3)/2)

Is there an easy way to prove this without getting lost in infinite series calculations, or is there a proof already in print?

Last edited by a moderator: